Challenges and Opportunities of Big Data Analytics for Upcoming Regulations and Future Transformation of the Shipping Industry. (2017) - Zaman, Ibna; Pazouki, Kayvan; Norman, Rose; Younessi, Shervin; Coleman, Shirley
Abstract: Shipping is a heavily regulated industry and responsible for around 3% of global carbon emissions. Global trade is highly dependent on shipping which covers around 90% of commercial demand. Now the industry is expected to navigate through many twists and turns of different situations like upcoming regulations, climate change, energy shortages and technological revolutions. Technological development is apparent across all marine sectors due to the rapid development of sensor technology, IT, automation and robotics. The industry must continue to develop at a rapid pace over the next decade in order to be able to adapt to upcoming regulations and market pressure. Ship intelligence will be the driving force shaping the future of the industry. Ships generate a large volume of data from different sources and in different formats. So big data has become the talk of the industry nowadays. Big data analysis discovers correlations between different measurable or unmeasurable parameters to determine hidden patterns and trends. This analysis will have a significant impact on vessel performance monitoring and provide performance prediction, real-time transparency, and decision-making support to the ship operator. Big data will also bring new opportunities and challenges for the maritime industry. It will increase the capability of performance monitoring, remove human error and increase interdependencies of components. However, the industry will have to face many challenges such as data processing, reliability, and data security. Many regulations rely on ship data including the new EU MRV (Monitoring, Reporting and Verification) regulation to quantify the CO2 emissions for ships above 5000 gross tonnage. As a result, ship operators will have to monitor and report the verified amount of CO2 emitted by their vessels on voyages to, from and between EU ports and will also be required to provide information on energy efficiency parameters. The MRV is a data-oriented regulation requiring ship operators to capture and monitor the ship emissions and other related data and although it is a regional regulation at the moment there is scope for the International Maritime Organisation (IMO) to implement it globally in the near future.